2021
DOI: 10.4103/apjon.apjon-2132
|View full text |Cite|
|
Sign up to set email alerts
|

Health-Promoting Lifestyle in Colorectal Cancer Survivors: A Qualitative Study on the Experiences and Perspectives of Colorectal Cancer Survivors and Healthcare Providers

Abstract: Objective: Understanding the experiences of survivors and healthcare providers about health-promoting lifestyle (HPL) in colorectal cancer (CRC) survivors is important in planning for coping with the disease, managing treatment side effects, increasing survival, and improving quality of life (QOL). This study was conducted to explore the experiences and perspectives of CRC survivors and healthcare providers about HPL in CRC survivors. Methods: This descriptive qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…(6) Patients could cooperate with the comprehensive therapeutic strategies in the MDT mode. Exclusion criteria are as follows: (1) patients with metastasis in vitals such as abdominal cavity and liver, (2) patients with dysfunction in vitals, (3) patients with the second primary tumor, (4) patients with the contraindication of chemotherapy, (5) patients with the contraindication of nutrition support, (6) patients with language dysfunction and who could not communicate with others, (7) patients with low immune function before chemotherapy and poor tolerance to chemotherapy, and (8) patients with endocrine system diseases 2.3. General Information.…”
Section: Inclusion and Exclusion Criteria Inclusion Criteria: (1)mentioning
confidence: 99%
See 1 more Smart Citation
“…(6) Patients could cooperate with the comprehensive therapeutic strategies in the MDT mode. Exclusion criteria are as follows: (1) patients with metastasis in vitals such as abdominal cavity and liver, (2) patients with dysfunction in vitals, (3) patients with the second primary tumor, (4) patients with the contraindication of chemotherapy, (5) patients with the contraindication of nutrition support, (6) patients with language dysfunction and who could not communicate with others, (7) patients with low immune function before chemotherapy and poor tolerance to chemotherapy, and (8) patients with endocrine system diseases 2.3. General Information.…”
Section: Inclusion and Exclusion Criteria Inclusion Criteria: (1)mentioning
confidence: 99%
“…Therefore, chemotherapy is recommended as the core treatment measure for patients with colon cancer in the guidelines of the National Comprehensive Cancer Network (NCCN) [ 4 ]. In recent years, the practice has gradually confirmed that adjuvant chemotherapy improves the median survival period of colon cancer patients, and the patients with liver metastasis benefit more especially [ 5 ]. However, patients with colon cancer often have multiple diseases before chemotherapy, and the incidence of malnutrition is about 40.0% [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for many cancer survivors with high survival rates, weight management, a healthy diet, and an active lifestyle are priorities for preventing the recurrence of primary cancers and other chronic diseases [7]. Improving lifestyle is highly important in the period after a cancer diagnosis because it is the time when survivors perceive the importance of changing their lifestyle and can change their behaviors, complete their primary treatment, including surgery and chemotherapy, and seek a healthy lifestyle to prevent repeated recurrence and promote survival [8,9].…”
Section: Introductionmentioning
confidence: 99%
“… 5 When side effects of early-onset treatments of cancer subside, consequences of cancer and treatment including negative body image and sexuality disorders, fatigue, anxiety, depression and psychological distress, physical and social limitations, and sensorineural dysfunction, which can last for years after the completion of treatment. 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%